Analysis of The Effect of Speed on Seakeeping and Ship Motion - Juswan Sade; Muhammad Syaifullah (Departemen of Ocean Engineering, Hasanuddin University, 2022)
Ship motion is the ability of a ship to survive at sea under any conditions. Therefore this capability is an essential aspect in terms of ship design. The shape of the hull dramatically influences the characteristics of the movement and operability of the ship itself. Vessel operability is the time at sea when the structure can still operate according to the established criteria and its correlation to the wave height where the requirements will be exceeded. In this study, an analysis of 3 degrees of freedom of translational movement and rotation of heave roll and pitch was carried out on the planing hull type fast boat model at regular waves with the parameters of body mass, gyration radius, damping, and others presented in the form of a Response Amplitude Operator (RAO) graphic image.